Knowledge management system for big data in a smart electricity grid context - Vinagre, Eugénia (2021)
We have been witnessing a real explosion of information, due in large part to the development in Information and Knowledge Technologies (ICTs). As information is the raw material for the discovery of knowledge, there has been a rapid growth, both in the scientific community and in ICT itself, in the study of the Big Data phenomenon (Kaisler et al., 2014). The concept of Smart Grids (SG) has emerged as a way of rethinking how to produce and consume energy imposed by economic, political and ecological issues (Lund, 2014). To become a reality, SGs must be supported by intelligent and autonomous IT systems to make the right decisions in real time. Knowledge needed for real-time decision-making can only be achieved if SGs are equipped with systems capable of efficiently managing all the surrounding information. Thus, this paper proposes a system for the management of information in the context of SG to enable the monitoring, in real time, of the events that occur in the ecosystem and to predict following events.